Pemanfaatan ekstrak air daun karamunting sebagai terapi tambahan pada penderita diabetes mellitus tipe II: edukasi dan pembuatan infusa/ekstrak air karamunting skala rumah tangga - Saleh, Muhammad Irsan; Lusiana, Evi; Rofflin, Eddy (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Utilisation of aqueous extract of karamunting leaves as adjunctive therapy in patients with type II diabetes mellitus: education and household-scale production of karamunting water infusion/extracts Diabetes mellitus (DM) is a chronic condition caused by high blood glucose levels due to insulin deficiency or the body's inability to use insulin properly. This community service aims to increase knowledge about Diabetes mellitus and the utilization of herbal plants Karamunting leaves to lower blood sugar. The target of the activity is the community in the working area of the Gandus Palembang Health Center, totaling 30 participants. The method in this service is in the form of socialization of herbal plants of Karamunting leaves to lower blood sugar. The results of this community service are an increase in knowledge and application of herbal plants of Karamunting leaves to reduce blood sugar in the community. The method used was counseling about diabetes mellitus and the benefits of Karamunting leaves, demonstration and assistance in making Karamunting leaf infusion, and evaluation. The results of this community service activity are knowledge about diabetes mellitus increased marked by the activeness of answering questions given and the independent use of Karamunting leaves in handling diabetes mellitus.